2022
DOI: 10.1177/23333928221117057
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant and Powerless: Exploring Barriers to Contraceptive use among Women in Mogadishu, Somalia

Abstract: Background With a maternal mortality ratio of 692 per 100 000 live births and modern contraception prevalence of 1%, understanding factors hindering Somali women from using modern contraception is key to developing and implementing locally adopted public health responses. The purpose of this qualitative study was to explore factors impeding Somali women in Mogadishu from using modern contraception Methods We conducted a qualitative study using semi-structured, in-depth interviews with 21 married women aged >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A study by [21] in Burkina Faso revealed that much as religious leaders have good knowledge about FP, they are reluctant to promote FP use. A study done in Somalia also revealed that religion is key barrier to access to FP [22].…”
Section: Discussionmentioning
confidence: 99%
“…A study by [21] in Burkina Faso revealed that much as religious leaders have good knowledge about FP, they are reluctant to promote FP use. A study done in Somalia also revealed that religion is key barrier to access to FP [22].…”
Section: Discussionmentioning
confidence: 99%
“…A study by [21] in Burkina Faso revealed that much as religious leaders have good knowledge about FP, they are reluctant to promote FP use. A study done in Somalia also revealed that religion is a key barrier to access to FP [22].…”
Section: Discussionmentioning
confidence: 99%
“… 6 Moreover, evidence exists of significant misconceptions among health-care providers, who discourage women from using contraception unless they have specific health concerns. 7 This situation diverges from other countries where health-care providers play a pivotal role in advocating for and facilitating increased contraceptive uptake. 8 …”
Section: Challengesmentioning
confidence: 98%